The Implementation of Quizizz Application as Formative Assessment for English Young Learners - Dewi, Nyoman Ayu Purnama (International Journal of Digital Learning on Languages and Arts (IJODLLA), 2025)
Formative assessment is important because it can be used to check the students’ progress in order to achieve the learning objective or learning goal. In 21stcentury, formative assessment can be easily conducted through applying technology. Quizziz application is one of MALL that can help the teacher to conduct formative assessment. The teacher at Lab UndikshaSingarajahad been using Quizziz application as a tool of formative assessment in the learning process. Meanwhile, there is lack of research disscussed about how the implementation of Quizziz application as formative assessment for Young English Learner. This study was intended to describe the implementation of Quizziz application as formative assessment for Young English Learner. Descriptive observational qualitative method is research design of this study. The results found that the teacher used scientific approach in conducting the lesson and applied the Quizziz application in “Experimenting” section. Quizziz application can help the teacher to conduct formative assessment because features of the application provides several information such as the students’ performance, how the questions work to the studentsand the students are also given feedback directly while they are asking the question which can catch the students’ interest and eager to answer the questions.